2019
DOI: 10.1093/gerona/glz008
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Therapeutic Tai Ji Quan Fall Prevention Intervention for Older Adults at High Risk of Falling

Abstract: Background Data on the cost-effectiveness of proven fall prevention exercise interventions are limited. We aimed to establish the cost-effectiveness of Tai Ji Quan: Moving for Better Balance (TJQMBB) compared with a conventional exercise intervention for older adults at high risk of falling. Methods We conducted a trial-based cost-effectiveness analysis involving 670 older adults who had a history of falling or impaired mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…32 Li and Harmer found that Tai Chi was both effective for reducing fall risk, 41 as well as a cost-effective method for reducing fall related injury in older adults with high risk of falling. 42 Similar findings have been reported across a broad range of older adults. 25,[43][44][45] However, in our study, there was no observed difference in fallrelated injuries among Tai Chi and HE groups.…”
Section: Discussionsupporting
confidence: 80%
“…32 Li and Harmer found that Tai Chi was both effective for reducing fall risk, 41 as well as a cost-effective method for reducing fall related injury in older adults with high risk of falling. 42 Similar findings have been reported across a broad range of older adults. 25,[43][44][45] However, in our study, there was no observed difference in fallrelated injuries among Tai Chi and HE groups.…”
Section: Discussionsupporting
confidence: 80%
“…One possible explanation may be because TCQ has been used as costeffective healing/exercise therapies for health promotion and disease prevention. [39][40][41] Another interesting nding in our study is that the more signi cant change is for people who have been physically inactive compared with people who have been doing some physical activities and/or regular physical activities from 2012 to 2017. This may be because more and more people are aware of the unique qualities of TCQ, as they involve the form of physical activity (i.e., graceful body movement).…”
Section: Discussionmentioning
confidence: 60%
“…Finally, our study also suggests that although both TJQMBB and multimodal exercise are associated with reduced incidence of injurious falls, the former has the additional advantage of requiring few resources for program implementation (eg, no equipment required, low costs, 20 and minimal space needed), thereby enhancing return on investment 28 and cost-effectiveness. 29 …”
Section: Discussionmentioning
confidence: 99%